The Influence of Content Marketing on the Loyalty of Valorant Game Users at X-Gate - TJANDRA, Anthony; WONO, Hilda Yunita (International Journal of Environmental, Sustainability, and Social Science, 2024)
In 2020, there is a new game called Valorant coming to Indonesia. Valorant is a first person shooter game that focuses on strategy, cooperation and player accuracy. Valorant Upload videos/images on their Twitter to introduce Valorant. Until now, the Valorant social media team continues to post content on their Twitter to attract more people. There are various types of content produced. From this variety of content, people are starting to get to know Valorant and try the game. Some of those who have tried still play Valorant to this day. So researchers want to know the influence of content marketing on the loyalty of Valorant game users using content marketing and loyalty theory and using the descriptive analysis method by deploying Google forms as a data collection tool for Valorant game users at X-gate Surabaya.